Crete reclaimed : a feminist exploration of bronze age Crete - Evasdaughter, Susan; Castleden, Rodney; Walker-John, Billie (Loughborough: Heart of Albion Press, 1996)
"Susan Evasdaughter ; foreword by Rodney Castleden ; illustrated by Billie Walker-John Bibliotheek François Vercammen"